Disentangling the effect of host genetics and gut microbiota on resistance to an intestinal parasite. Issue 11 (October 2019) - Faivre, Bruno; Bellenger, Jérôme; Rieu, Aurélie; Guivier, Emmanuel; Galan, Maxime; Ollivier, Anthony; Poloni, Lauriane; Sorci, Gabriele
Graphical abstract: Highlights: Mouse strain remained the main factor accounting for resistance to Heligmosomoides polygurus. The mouse gut microbiota played a strain-specific role that explains host susceptibility. A gut microbiota transplant increased resistance of the more susceptible mouse strain. Abstract: Resistance to infection is a multifactorial trait, and recent work has suggested that the gut microbiota can also contribute to resistance. Here, we performed a fecal microbiota transplant to disentangle the contribution of the gut microbiota and host genetics as drivers of resistance to the intestinal nematode Heligmosomoides polygyrus . We transplanted the microbiota of a strain of mice (SJL), resistant to H. polygyrus, into a susceptible strain (CBA) and vice-versa. We predicted that if the microbiota shapes resistance to H. polygyrus, the FMT should reverse the pattern of resistance between the two host strains. The two host strains had different microbiota diversities and compositions before the start of the experiment, and the FMT altered the microbiota of recipient mice. One mouse strain (SJL) was more resistant to colonization by the heterologous microbiota, and it maintained its resistance profile to H. polygyrus (lower parasite burden) independently of the FMT. On the contrary, CBA mice harbored parasites with lower fecundity during the early stage of the infection, and had an up-regulated expression of the cytokine IL-4 (a marker of H. polygyrus resistance) after receiving the heterologous microbiota. Therefore, while host genetics remains the main factor shaping the pattern of resistance to H. polygyrus, the composition of the gut microbiota also seems to play a strain-specific role.